A verse by Virgilio Pinera in the creativeness of Reinaldo Arenas: from “La isla en peso” to El color del verano - López Cruz, Humberto (2016)
This work attempts to approach Reinaldo Arenas’ The Color of Summer by means of a possible poetic displacement. In his autobiography, the Cuban writer makes subtle comments that point towards a labyrinth of textual permutations that, perhaps, connect with a verse from Virgilio Piñera’s timeless poem “The Whole Island.” This essay, thus, creatively retraces the steps that lead to the origin of the novel’s idea, that is the seed from which The Color of Summer sprouted. In order to understand Arenas’ hyperbolic narrative, one must first return to Piñera’s canonical poem, published in 1943, which portrayed the island and its inhabitants as protagonists. A comparison reveals a parallel that begins to delineate itself between both texts: the poem singing about the island in its totality and the prose depicting how the weight of the foundation-less island forces it to sink into the sea. Ultimately, this modified idea from a verse in Piñera’s poem becomes the outcome of the novel by Arenas.